Novel Electroforming‐Free Nanoscaffold Memristor with Very High Uniformity, Tunability, and Density. (28th July 2014) - Lee, Shinbuhm; Sangle, Abhijeet; Lu, Ping; Chen, Aiping; Zhang, Wenrui; Lee, Jae Sung; Wang, Haiyan; Jia, Quanxi; MacManus‐Driscoll, Judith L.
<x xml:space="preserve">Abstract</x> A novel device structure is developed, which uses easy‐to‐grow nano scaffold films to localize oxygen vacancies at vertical heterointerfaces. The strategy is to design vertical interfaces using two structurally incompatible oxides, which are likely to generate a high‐concentration oxygen vacancy. Non‐linear electroresistance at room temperature is demonstrated using these nano scaffold devices. The resistance variations exceed two orders of magnitude with very high uniformity and tunability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>